Graphene: Guiding Stem Cell Differentiation into Oligodendrocytes Using Graphene‐Nanofiber Hybrid Scaffolds (Adv. Mater. 22/2014). (June 2014) - Shah, Shreyas; Yin, Perry T.; Uehara, Thiers M.; Chueng, Sy‐Tsong Dean; Yang, Letao; Lee, Ki‐Bum
<x xml:space="preserve">Abstract</x> By combining the unique properties of nanofibers and graphene‐based nanomaterials in a single biocompatible scaffold, K.‐B. Lee and co‐workers report the selective differentiation of stem cells into mature oligodendrocytes on page 3673. Given the role of oligodendrocytes in myelinating the axon of a neuron, these graphene‐nanofiber hybrid scaffolds may prove to be useful in treating injuries and diseases of the central nervous system. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>